Underwater laser cutting of stainless steel up to 100 mm thick for dismantling application in nuclear power plants. (November 2020) - Shin, Jae Sung; Oh, Seong Yong; Park, Seungkyu; Park, Hyunmin; Kim, Taek-Soo; Lee, Lim; Kim, Yonghee; Lee, Jonghwan
Highlights: An underwater laser cutting study was performed for dismantling application in nuclear power plants. Stainless steel specimens were cut up to 100 mm in thickness using a fiber laser with a power of 9 kW. Excellent performance was obtained in terms of cutting speed and thickness even in an underwater environment. The results obtained in this study are expected effectively used in actual nuclear power plant decommissioning sites. Abstract: For dismantling nuclear power plants, an underwater cutting study was conducted using a high power fiber laser. With a laser power of 9 kW, cutting tests were performed on stainless steel with a thickness of 50–100 mm. For this study, a waterproof cutting head consisting of a focusing element with a long focal length of 600 mm and a supersonic nozzle was used for high cutting efficiency. For thicknesses of 70 mm or less, it was possible to cut only with a single supersonic nozzle, while for a thickness of 80 mm or more, an initially pierced specimen or a double nozzle was required for successful cutting. Through these techniques, we were able to perform the cutting underwater up to a thickness of 100 mm. Furthermore, the kerf widths were as small as 1–2 mm, the amount of secondary waste will likely be small, which will reduce waste disposal costs.